2015
DOI: 10.5539/elt.v8n8p79
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical Significance of Morphological Awareness in Korean and English

Abstract: This study investigated whether Korean children understand the internal structure of compound words in Korean and English and whether there is a relationship between their performance in tasks that measure their understanding of the morphological structure of compounds in Korean and English. This study also examined the effects of gender, grade, and verbal ability on the performance of the Korean and English tasks. 106 primary school children completed a Korean and English compound task, which consisted of 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 43 publications
1
6
1
Order By: Relevance
“…This provides evidence of similarities in English and Norwegian, and across primary and middle school. Our finding that receptive and productive knowledge make up two of these factors is also in line with González‐Sánchez et al (2018) and Jong and Jung (2015), indicating similarities with Spanish children in preschool as well as with Korean fifth and sixth graders. This separation of receptive and productive knowledge may, however, represent construct‐irrelevant variance due to differences between general comprehension and language production, rather than separate dimensions of morphological knowledge.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This provides evidence of similarities in English and Norwegian, and across primary and middle school. Our finding that receptive and productive knowledge make up two of these factors is also in line with González‐Sánchez et al (2018) and Jong and Jung (2015), indicating similarities with Spanish children in preschool as well as with Korean fifth and sixth graders. This separation of receptive and productive knowledge may, however, represent construct‐irrelevant variance due to differences between general comprehension and language production, rather than separate dimensions of morphological knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Other studies have found support for a multidimensional structure of morphological knowledge (González‐Sánchez et al, 2018; Jong & Jung, 2015; Levesque et al, 2017; Tighe & Schatschneider, 2015, 2016; Zhang, 2017). Both González‐Sánchez et al (2018) and Jong and Jung (2015) reported separate dimensions of receptive and productive morphological knowledge in their studies. Their studies targeted Spanish children in the last year of preschool (González‐Sánchez et al, 2018) and Korean fifth and sixth graders (Jong & Jung, 2015).…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations